THE MODEL OF TEACHING FUTURE PHILOLOGISTS DISCUSSION IN ENGLISH BASED ON PROBLEMATIC SITUATIONS - Ірина Зайцева; Марія Писанко (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The article deals with the model of teaching 1-st year students of foreign languages' faculties discussion based on problematic situations and the ways of implementing such a model in the teaching process at the English language classes. The author defines and describes principles and stages of teaching discussion, hours for students' class and individual work (autonomous learning), techniques and methods of teaching. Such notions as "model", "communicative-discussion skills" and "method of teaching" have been defined. The gradual implementation of the model of learning process in terms of credit-modular system of training is described. The purpose, object and subjects of study that are important for creating a model of teaching discussion to future philologists based on problematic situations have been singled out.